ANALISIS MULTIPLAYER EFFECT KEBERADAAN PELABUHAN PERIKANAN TERHADAP EKONOMI USAHA KULINER DI PANGKALAN PENDARATAN IKAN BEBA, KEC. GALESONG UTARA, KAB. TAKALAR - Muh Ramli; Danial Danial; Ihsan Ihsan (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
This study aims to identify the types of economic activity, characteristics and perceptions of visitors, business actors, labor towards culinary businesses and to determine the multiplier effect and sustainable development strategies for culinary businesses on the economic growth of local communities. This research was conducted from November 2020 to January 2021 at the Beba Fish Landing Base, Galesong Utara, Takalar Regency. This research uses simple random sapling technique. The data of this study consisted of primary data and secondary data. Data collection was carried out using questionnaires and field observations then analyzed descriptively and multiple impact analysis (Multiplier Effect) then analyzed using a SWOT analyst. Based on the research results, there are two types of economic activities in PPI Beba, namely, fishery activities and supporting activities (culinary business) of food made from fish as the main ingredient. In general, visitors who come to PPI Beba are aged between 45 years and over with the majority of jobs being civil servants with 51% of the total visitors as a whole the rest are entrepreneurs. While the majority of business actors are women in the age range of 40 - 50 years and over. Meanwhile, 81.8% of the culinary business workforce are women with the highest level of education in Elementary Schools. In general, the three recipes gave an assessment of the PPI Beba condition which was far from good. is the main business. The characteristics of the workforce are 74.3% female and 25.7% male, with the status of 65.7% being married and ages ranging from 28 - 45 years. And in general, visitors have a perception or give a moderate to good assessment of the accessibility to PPI Beba. Culinary efforts at PPI Beba have a real economic impact on the local community. The economic impacts arising from these activities are direct impacts, indirect impacts, and induce impacts as measured by the multiplier effect value, where the results of this study obtained a multiplier effect value of 2.15 for the Keynesian Income Multiplier; 1.10 for the income multiplier type I ratio, and 1.14 for the income multiplier type II ratio. This shows that the culinary business at PPI Beba can be developed into culinary tourism to see the opportunities that exist.